Systemic Administration of Glibenclamide Fails to Achieve Therapeutic Levels in the Brain and Cerebrospinal Fluid of Rodents. - Carolina Lahmann; Holger B Kramer; Frances M Ashcroft (PLoS ONE)
Activating mutations in the Kir6.2 (KCNJ11) subunit of the ATP-sensitive potassium channel cause neonatal diabetes (ND). Patients with severe mutations also suffer from neurological complications. Glibenclamide blocks the open KATP channels and is the treatment of choice for ND. However, although glibenclamide successfully restores normoglycaemia, it has a far more limited effect on the neurological problems. To assess the extent to which glibenclamide crosses the blood-brain barrier (BBB) in vivo, we quantified glibenclamide concentrations in plasma, cerebrospinal fluid (CSF), and brain tissue of rats, control mice, and mice expressing a human neonatal diabetes mutation (Kir6.2-V59M) selectively in neurones (nV59M mice). As only small sample volumes can be obtained from rodents, we developed a highly sensitive method of analysis, using liquid chromatography tandem mass spectrometry acquisition with pseudo-selected reaction monitoring, achieving a quantification limit of 10ng/ml (20nM) glibenclamide in a 30μl sample. Glibenclamide was not detectable in the CSF or brain of rats after implantation with subcutaneous glibenclamide pellets, despite high plasma concentrations. Further, one hour after a suprapharmacological glibenclamide dose was administered directly into the lateral ventricle of the brain, the plasma concentration was twice that of the CSF. This suggests the drug is rapidly exported from the CSF. Elacridar, an inhibitor of P-glycoprotein and breast cancer resistance protein (major multidrug resistance transporters at the BBB), did not affect glibenclamide levels in CSF and brain tissue. We also identified a reduced sensitivity to volatile anaesthetics in nV59M mice and showed this was not reversed by systemic delivery of glibenclamide. Our results therefore suggest that little glibenclamide reaches the central nervous system when given systemically, that glibenclamide is rapidly removed across the BBB when given intracranioventricularly, and that any glibenclamide that does enter (and is below our detection limit) is insufficient to influence neuronal function as assessed by anaesthesia sensitivity.